Rapid removal of chromium (VI) from aqueous solution using iron oxide/polyaniline nanocomposites - Thao, Vu Dinh; Thao, Pham Manh (Vietnam Journal of Chemistry, 2015)
Core-shell structured magnetic iron oxide nanoparticles/polyaniline (Fe3O4 NPs/PANi) nanocomposite has been successfully synthesized by a two-step chemical precipitation-polymerization route, and was characterized using transmission electron microscopy (TEM), Fourier transform infrared spectra (FT-IR), and X-ray diffraction (XRD). Fe3O4 NPs/PANi nanocomposite was used as adsorbent to remove hexavalent chromium (Cr(VI)) ions from aqueous solution.The equilibrium data were well fitted the Langmuir isotherm model. The maximum adsorption capacity of Fe3O4 NPs/PANi nanocomposite for Cr(VI) is 76.9 mg.g-1. The adsorption mechanism has been identified as an ion exchange and a redox mechanism, based on X-ray photoelectron spectroscopy (XPS) study. Our study shows that magnetic Fe3O4 NPs/PANi nanocomposite is a promising adsorbent for rapid removal of Cr(VI) from aqueous solution.